The use of 3d printing technology in the development of a prosthetic thumb - Rezmer, Jakub; Wasilewska, Inga; Świątek, Łukasz (Journal of Education, Health and Sport, 2022)
Introduction: Over the years, the popularisation of 3D printing technology created new possibilities for developing customized and cheap prosthetics in a shorter time than time-consuming and expensive conventional methods. With the available software and knowledge, there are limitless possibilities for tailoring every prosthetic exclusively to the patient when keeping the costs reasonably low. Objective: The objective of the study was to research, review and compare data available on PubMed about the use of 3D printing in the development of a prosthetic thumb. A brief description of the state of knowledge: Conventional methods of prosthetic manufacture require a skilled professional prosthetist, a lot of time, and the costs from 4000-8000$ for a body-powered one, to 25000-50000$ for an externally powered one. That could be a major financial barrier for a patient. The 3D printing technology development over the last 15 years provided a fast and cheap method of manufacture for low-batch prosthetics, including thumb prosthetics, while being able to easily alter the project to customize it to the patient’s needs. Conclusions: There is a possibility to create fully functioning and durable thumb prosthetics with 3D printing technology. However, we need more research to provide a universal and fully customizable one to meet every patient's needs.